Placental serotonergic system dysregulation is associated with early impairments in infant neurodevelopment - Canul-Euan, Arturo A.; Flores-Pliego, Arturo; Solis-Paredes, Juan M.; Espejel-Nuñez, Aurora; Parra-Hernández, Sandra B.; Mendoza-Hernández, Tahiri; Hernandez-Chavez, María del Carmen; Gil-Martínez, Gabriela; Zamora-Sánchez, Carmen J.; Perichart-Perera, Otilia; Estrada-Gutierrez, Guadalupe; Camacho-Arroyo, Ignacio (Frontiers in Endocrinology, 2025)
IntroductionSerotonin (5-hydroxytryptamine [5-HT]) plays a fundamental role in fetal neurodevelopment. While 5-HT is synthesized in the fetal brain, the placenta contributes significantly to fetal 5-HT levels during early gestation. However, little is known about the influence of placental serotonergic components on early neurodevelopmental outcomes. In this study, we have evaluated the association between the expression of key components of the placental serotonergic system and neurodevelopmental status in infants of mother–child dyads enrolled in the Origen Bioquı́mico y Epigenético del Sobrepeso y la Obesidad (OBESO) perinatal cohort at the first month of life.MethodsWe analyzed 5-HT concentrations in maternal serum, umbilical cord serum, and placental tissue, and investigated the expression of key proteins of the serotonergic system in the placenta. All samples were obtained from full-term healthy pregnancies. 5-HT levels were measured by ELISA, and protein expression in placental tissue was evaluated by Western blot. Neurodevelopment was assessed at 1 month of age using the Bayley Infant Development Scale III (BSID-III). Infants with two or more BSID-III domain scores ≤ 7 were grouped as having altereded neurodevelopment.ResultsPlacentas from infants with altered neurodevelopment exhibited higher expression of tryptophan hydroxylase types 1 and 2 (TPH1 and TPH2)—the rate-limiting enzymes in 5-HT synthesis—as well as the serotonin transporter (SERT), compared to those from infants with normal neurodevelopment. In contrast, expression of monoamine oxidase-A (MAO-A), the primary degrading enzyme, was significantly lower in the altered group. Interestingly, 5-HT levels and the expression of 5-HT1E and 5-HTR5A receptors were similar between groups.ConclusionThese findings suggest that dysregulation of the placental serotonergic system, independent of total 5-HT levels, could be associated with early neurodevelopmental impairments, highlighting the importance of placental serotonin signaling in fetal brain development.